Jenis-Jenis Semut (Hymenoptera: Formicidae) di Bangunan Kampus Universitas Andalas Limau Manis Padang - Anna Febry Astuti; Henny Herwina; - Dahelmi (Universitas Andalas, 2014)
Study about ants species (Hymenoptera: Formicidae) at campus building was conducted in Andalas University Limau Manis Padang from September 2012 to April 2013. Direct collection method and baited traps were used to collect ants at 12 building. A total of 11 species that belonging to four subfamily, six tribe, and 11 genera and 859 individual of ant was collected. Myrmicinae was the highest in number of species (four species), followed by Dolichoderinae (three species) only two species were found as Formicinae and Ponerinae. Six of collected species are recognized as ant pests. Keywords: ant, pest, campus, building